14.0k views
2 votes
Please find the answer , it is a very importatnt question

Please find the answer , it is a very importatnt question-example-1

1 Answer

2 votes

Explanation:

The given expression is :


(2-\sqrt5)/(2+3\sqrt5)=\sqrt5 x+y ....(1)

Taking LHS of the above expression


(2-\sqrt5)/(2+3\sqrt5)

Rationalizing both denominator and numerator.


(2-\sqrt5)/(2+3\sqrt5)* (2-3\sqrt5)/(2-3\sqrt5)=(4-6\sqrt5-2\sqrt5+15)/(2^2-(3\sqrt5)^2)\\\\=(19-8\sqrt5)/(4-45)\\\\=(19-8\sqrt5)/(-41)\\\\=(\sqrt5 * 8)/(41)+((-19)/(41))

Equation (1) becomes,


(\sqrt5 * 8)/(41)+((-19)/(41))=\sqrt 5\ x+y

Equating both sides,


x=(8)/(41) and
y=(-19)/(41)

Hence, this is the required solution.

User Grigno
by
4.6k points